THU0153 Improvements in disease activity score by baseline status: Pooled analysis of five phase 3 studies with tofacitinib (CP-690, 550) in patients with active rheumatoid arthritis. (23rd January 2014) - Fleischmann, R.M.; Krishnaswami, S.; Gruben, D.; Zwillich, S.H.; Mebus, C.; Bradley, J.D.
Abstract : Background: Tofacitinib (CP-690, 550) is a novel, oral Janus kinase inhibitor being investigated as a targeted immunomodulator in rheumatoid arthritis. Objectives: To assess efficacy of tofacitinib 5 and 10 mg twice-daily (BID) using disease activity scores (DAS) across a wide range of baseline (BL) values. Methods: Demographic and BL disease characteristics of patients (pts) in five Phase 3 studies (monotherapy: NCT00814307 ; background DMARD: NCT00960440, NCT00847613, NCT00856544, NCT00853385 ) were similar. Data were pooled, and BL DAS values based on 28-joint counts using C-reactive protein (DAS28-3(CRP)) were divided into four groups (≤25th, >25th-50th, >50th-75th, >75th percentiles); for each, mean change from BL, proportion of pts improving by ≥1.2 from BL, and proportions of pts with values ≤3.2 and <2.6 at Month 3 were computed for placebo (PBO), 5 mg BID and 10 mg BID. Observed data (no imputations) were analysed. Results: 3072 pts (PBO, 673; 5 mg, 1200; 10 mg, 1199) were divided into groups using BL DAS28-3(CRP) quartiles: ≤4.71 (Q1); >4.71-5.34 (Q2); >5.34-6.01 (Q3); >6.01 (Q4). In each group, both tofacitinib doses demonstrated clinically significant improvements in DAS28-3(CRP)-based analyses compared with PBO. Pts with higher BL values had greater mean reductions in DAS, with correspondingly larger differences from PBO. All BL groups showed numerical benefit of 10 mg BID over 5 mg BID across all DAS28-3(CRP)-based analyses and the proportions of pts achieving various DAS thresholds were 2-13 percentage points greater with 10 mg BID vs 5 mg BID. Data for Q1 and Q4 are shown in Table 1 . Conclusions: Across a range of BL disease activities, tofacitinib was consistently efficacious at both doses in reducing DAS28-3 (CRP) vs PBO. All groups showed numerical benefit in efficacy of 10 mg BID over 5 mg BID across all measures of DAS28-3 (CRP); the magnitude of benefit of 10 mg BID over 5 mg BID appeared to be independent of BL status. As expected, pts in the lowest quartile were more likely to achieve DAS28-3(CRP) ≤3.2 and <2.6 than pts in the highest quartile. Even though pts with higher BL disease activity reached the target to a lesser extent, it remains achievable in this population. Similar analyses of other composite disease activity indices are required to confirm these results. Disclosure of Interest: R. Fleischmann Grant/Research support from: Pfizer Inc, Consultant for: Pfizer Inc, S. Krishnaswami Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, D. Gruben Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, S. Zwillich Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C. Mebus Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, J. Bradley Shareholder of: Pfizer Inc, Employee of: Pfizer Inc